Social Cognition in Multiple Sclerosis Is Associated to Changes in Brain Connectivity: A Resting-State Fmri Study - Labbe-Atenas, T (Elsevier B.V., 2020)
Background: Multiple Sclerosis produces changes in the functional connectivity of the brain. Resting-State fMRI is a useful tool for the study of functional changes in the human brain, and its metrics can be related to clinical findings involved in clinical decline. Social cognition has focused increasing interest because patients are exposed to experiencing social disorganization during the progression of the disease. fMRI has proved to be a useful tool for studying brain connectivity and its relation with social cognition both in resting-state and during socio-cognitive tasks. Objective. to identify functional changes during rest in Relapsing-Remitting Multiple Sclerosis patients and look for a correlation with social cognition. Methods. 45 patients with Relapsing-Remitting Multiple Sclerosis and 47 control subjects were recruited to perform a neuropsychological evaluation of the social cognition performance and to acquire resting-state fMRI. Results. Patients exhibited lower performance in social cognition tasks, mostly related to face emotion recognition. Decreased functional connectivity in patients is seen concerning the right anterior insula, middle frontal, and occipital regions while increased connectivity is mostly related to the occipital and visual areas. The connectivity of the fusiform cortex and the amygdala is related to the performance in emotion recognition and Theory of Mind tasks respectively. Conclusion. Social cognition compromise was found in this sample. Functional connectivity changes during rest were detected and correlated with social cognition changes in patients. © 2020 Elsevier B.V.